The greatest military reversal of South African arms: the fall of Tobruk 1942, an avoidable blunder or an inevitable disaster? - Katz, David (Faculty of Humanities, University of the Free State, 2012)
The surrender of Tobruk 70 years ago was a major catastrophe for the Allied war effort, considerably weakening their military position in North Africa, as well as causing political embarrassment to the leaders of South Africa and the United Kingdom. This article re-examines the circumstances surrounding and leading to the surrender of Tobruk in June 1942, in what amounted to the largest reversal of arms suffered by South Africa in its military history. By making use of primary documents and secondary sources as evidence, the article seeks a better understanding of the events that surrounded this tragedy. A brief background is given in the form of a chronological synopsis of the battles and manoeuvres leading up to the investment of Tobruk, followed by a detailed account of the offensive launched on 20 June 1942 by the Germans on the hapless defenders. The sudden and unexpected surrender of the garrison is examined and an explanation for the rapid collapse offered, as well as considering what may have transpired had the garrison been better prepared and led.
Keywords: South Africa; HB Klopper; Union War Histories; Eighth Army; 1st South African Division; Court of Enquiry; North Africa; Gazala; Freeborn